A Mathematical Law for Assessing Outcome Values of Games. (June 2014) - Dickinson, John R.
Background: The predominate outcomes of manycomputerized simulation games, particularlybusiness games, are numeric values, for example, financial statements, as determined by thegame algorithm . Numerous types of algorithms have been put forth. Attending these algorithms are issues of their validity; numerous approaches tovalidation also having been put forth. Aim: This research presents a type ofdigital analysis, Benford's Law, as a basis for assessing the validity of simulation gamenumeric outcome values, that is, algorithmic validity . Method: To illustrate the application of Benford's Law, it was applied to income statement items from a business game competition. Thefirst digits andsecond digits, respectively, of numeric outcome values were analyzed. Results: Both the first digits and the second digitsconform closely toBenford's Law . Less conforming outcomes were those of assigned values to which Benford's Law does not apply. Conclusion: Benford's Law is conceptually and practicallyappropriate forassessing simulation gamenumeric outcome values . An example of its application demonstrates this appropriateness.